Hunt for the origin of allergy - comparing the Finnish and Russian Karelia. - Haahtela, T.; Laatikainen, T.; Alenius, H.; Auvinen, P.; Fyhrquist, N.; Hanski, I.; von Hertzen, L.; Jousilahti, P.; Kosunen, T. U.; Markelova, O.; Mäkelä, M. J.; Pantelejev, V.; et al. (Clinical & Experimental Allergy, 2017)
The Finnish and Russian Karelia are adjacent areas in northern Europe, socio-economically distinct but geoclimatically similar. The Karelia Allergy Study was commenced in 1998 to characterize the allergy profiles in the two areas. Allergy prevalence had increased in Finland since the early 1960s, but the situation in Russia was unknown. The key finding was that allergic symptoms and diseases were systematically more common in Finnish children and adults than in their Russian counterparts. For example, in the early 2000s, hay fever in school children was almost non-existent in Russian Karelia, and only 2% were sensitized to birch pollen compared with 27% in Finnish Karelia. Adult birth cohorts showed that among those born in the 1940s, the sensitization to pollens and pets was at the same low level in both countries, but among younger generation born in the late 1970s, the difference was already manifold. Seropositivity to some pathogens, microbial content in house dust and drinking water seemed to confer allergy protection in Russia. In subsequent studies, it became apparent that on the Finnish side, healthy children had a more biodiverse living environment as well as greater diversity of certain bacterial classes on their skin than atopic children. Abundance of skin commensals, especially Acinetobacter (gammaproteobacteria), associated with anti-inflammatory gene expression in blood leucocytes. In vivo experiments with the mouse model demonstrated that intradermally applied Acinetobacter protected against atopic sensitization and lung inflammation. These observations support the notion that the epidemic of allergy and asthma results from reduced exposure to natural environments with rich microbiota, changed diet and sedentary lifestyle. Genetic studies have confirmed strong influence of lifestyle and environment. With our results from the Karelia study, a 10-year National Allergy Programme was started in 2008 to combat the epidemic in Finland. Peer reviewed